No role of working memory in the relation between mental rotation and postural stability - Hofmann, Philipp; Siebertz, Markus; Jansen, Petra (Frontiers in Cognition, 2024)
This study investigated the relationship between mental rotation ability and postural stability, with a focus on the role of the visuospatial sketchpad of working memory, as it has been found to be correlated with both concepts. A total of 87 healthy young adults completed a postural stability task on a force plate, a mental rotation task, and both spatial and object working memory tasks in a counterbalanced order. Bayesian correlations revealed weak positive correlations between mental rotation and postural stability, as well as a correlation between mental rotation and spatial working memory. A weak association was also observed between mental rotation and object working memory. No correlation was found between the working memory components and postural stability. Furthermore, the results showed that spatial working memory did not play a crucial role in predicting postural stability. We conclude that the visuospatial sketchpad, particularly the spatial working memory component, cannot explain the relationship between mental rotation and postural stability.